The invisible world [videorecording] - Kane, Dennis B.; Pomasanoff, Alex; Skinner, Thomas (National Geographic Society Special., 1979)
A documentary which examines the universe of shapes, movements, and lives that exist beyond the limited range of human vision by using highly specialized cameras, imaging devices, and lectron microscopes.